(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Adnan, Navia ZI, Silvia M, Antika M, Suwardi AB, Baihaqi, Yakob M. 2022. Diversity of herbs and spices plants and their importance in traditional medicine in the South Aceh District, Indonesia. Biodiversitas 23: 3836-3843. Kluet people are one of the ethnic communities living in Southern Aceh, Indonesia. Various herbs and spices plants are used by the Kluet people as a traditional medicine in treating diseases and disorders. The study aimed to investigate the diversity of herbs and spices plants and their importance in the traditional medical system. It was based on field surveys, plant collection, and semi-structured interviews with the local people. Interviews were performed with 355 informants selected by using the random sampling technique. A total of 30 medicinal plant species, consisting of 18 families, have been documented. Curcuma longa, Kaempferia galanga, Zingiber officinale, Citrus x aurantiifolia, Alpinia galanga, Averrhoa bilimbi, Elettaria cardamomum, Allium sativum, Cocos nucifera, and Syzygium aromaticum are the most popular medicinal plants known by Kluet people. More than 40% of traditional knowledge related to the use of herbs and spices as traditional medicine was obtained from their families/friends/neighbors. Traditional knowledge is thought to decline among generations. It is supposedly due to lifestyle changes as a result of modernization. The documentation and promotion of traditional medicine systems through formal and non-formal education may contribute to the conservation of biodiversity and traditional knowledge.